Antiarrhythmic Activity of Amino Acids Containing Nibentan Derivatives in Case of Symptoms of Occlusive and Reperfusion Arrhythmias - S. M. Napalkova; O. V. Buyuclinskaya (Разработка и регистрация лекарственных средств)
Introduction. Pharmacotherapy of cardiac arrhythmias is one of the urgent problems of modern medicine. The presence of serious side effects, in particular proarrhythmic action, limits the use of known antiarrhythmics in clinical practice. One way to reduce the toxicity of pharmacological agents is to use them as complex compounds with amino acids.Aim. Studying the effect of nibentan derivatives containing magnesium salt of L-aspartic acid and glycine as anions on the course of early occlusive and reperfusion arrhythmias.Materials and methods. Aminоacid derivatives of nibentan have been studied in models of occlusive and reperfusion arrhythmias in rats. The activity of the drugs was assessed by the incidence of ventricular extrasystoles (VEC), ventricular tachycardia (VT), ventricular fibrillation (VF), by the latent period and duration of arrhythmias, the average duration of VT, and by the number of VEC per 1 animal.Results and discussion. Nibentan derivatives in models of early occlusive and reperfusion arrhythmias were not inferior in antiarrhythmic activity to lidocaine and nibentan in their ability to prevent cardiac arrhythmias. The nibentan derivative containing the magnesium salt of L-aspartic acid (compound LHT-53-91) in the model of occlusive arrhythmias at a dose of 2 % LD50 completely prevented cardiac arrhythmias in experimental animals. A nibentan derivative containing glycine (compound LHT-20-92) at a dose of 1 % LD50 significantly reduced the number of cases of PVCs, prevented the occurrence of ventricular tachycardia and ventricular fibrillation in 100 % of cases. In the model of reperfusion arrhythmias, LHT-53-91 at a dose of 1 % LD50 prevented the development of ventricular fibrillation and paroxysms of ventricular tachycardia and reduced the risk of developing ventricular extrasystole (p < 0.05). Increasing the dose to 2 % LD50 led to an increase in the activity of the substance, which was expressed in the prevention of cardiac arrhythmias in 100 % of the animals. LHT-20-92 at a dose of 1 % LD50 in this model of cardiac arrhythmias statistically significantly reduced the occurrence of VES and VT paroxysms and completely prevented the occurrence of VF (p < 0.05).Conclusion. The inclusion of nibenthan amino acids in the structure, which shielded genotic grouping and reduced potential teratogenicity and mutagenicity, had not led to a reduction in the antiarrhythmic and antifibril-torn activity on the studied models of rhythm disorders.